POEM Is a Durable Treatment in Children and Adolescents With Achalasia Cardia - Nabi, Zaheer; Ramchandani, Mohan; Basha, Jahangeer; Goud, Rajesh; Darisetty, Santosh; Reddy, Duvvur Nageshwar (Frontiers in Pediatrics, 2022)
Background and aim: Per-oral endoscopic myotomy (POEM) is emerging as an effective treatment in pediatric achalasia. There is limited data on the long-term efficacy of POEM in children and adolescents with achalasia. In this study, we aim to evaluate the outcomes of POEM at ≥4-years follow-up. Method: The data of consecutive children who underwent POEM (September 2013 to July 2021) and completed at least four years follow-up were analysed, retrospectively. The primary outcome was clinical success (Eckardt≤3) at ≥4-years follow-up. The secondary outcomes included the prevalence of gastroesophageal reflux disease (GERD) and predictors of recurrent symptoms (Eckardt≥2) after POEM. Results: A total of 69 children underwent POEM for achalasia during the study period. Of these, 41 (59.4%) children completed ≥4-years [mean 68.5 months (range 48-94)] follow-up and 38 included in the final analysis. The subtypes of achalasia included type I (28.9%), type II (60.5%) and type III (2.6%). A history of prior treatment was present in 11 (28.9%). Clinical success was recorded in 36 (94.7%) patients who successfully underwent POEM. Recurrent symptoms (Eckardt ≥2) were noticed in 12 (31.6%) children at ≥4years. On multivariate analysis, there were no identifiable factors which predicted recurrent symptoms after POEM. Symptomatic GERD and erosive esophagitis were detected in 13.8%(4/29) and 57.1% (8/14) children, respectively. Conclusion: POEM is a durable treatment modality for achalasia in pediatric population irrespective of the sub-type of achalasia and history of prior treatment.